The Schengen information system and data retention : : on surveillance, security and legitimacy in the European Union - Orrù, Elisa (2017)
Abstract: As a technique of social control based on the collection of information, surveillance has been a central instrument of any administrative power since the modern era. Surveillance, however, can be carried out in different ways and these can provide important information on the basic features of a particular political system. Indeed, the introduction of surveillance measures has an impact on key relationships of a political system, such as liberty and security, autonomy and authority. When a political system is, like the European Union (EU), in a dynamic and build-up phase, by analysing its surveillance practices one can even discern the trajectories of its developments. The paper analyses two surveillance measures in the EU: the Schengen Information System (SIS) and the Directive 2006/24/EC on data retention. It puts forth the argument that the reference to security as a value enables the EU to compensate its legitimacy deficiencies and to develop into a power system characterised by a more supranational structure than before